CD73, a significant protein in liver diseases - Shi, Huilian; Dai, Heng; Sun, Qianqian; Wang, Siliang; Chen, Yuanyuan (Frontiers in Medicine, 2023)
Purine adenosine pathway exists widely in the body metabolism, and is involved in regulating various physiological processes. It is one of the important pathways of environmental regulation in human body. CD73 is essentially a protease that catalyzes further dephosphorylation of extracellular adenine nucleotides, hydrolyzing extracellular AMP to adenosine and phosphate. CD73 is an important part of the adenosine signaling pathway. Studies have shown that CD73-mediated adenosine pathway can convert the inflammatory ATP into the immunosuppressant adenosine. This paper aims to summarize the relevant effects of CD73 in the occurrence, development and prognosis of liver diseases such as viral hepatitis, highlight the important role of CD73 in liver diseases, especially in viral hepatitis such as HBV and HCV, and explore new clinical ideas for future treatment targets of liver diseases.